Up to date cultural practices in modern projective industries - A. A. Semenenko, (Ukrainian Cultural Studies, 2018)
The article analyzes the connection between some forming relevant tendencies and the newest cultural practices, the development of which is due to economical, technical and social context. Such features as mass character, consumerism, innovativeness, integrality, media character, network and information unity, fundamentally transform the image of civilization and people’s lifestyle. Human projective activity vectors are explored with terminological tools of cultural anthropology and civilizational movement dominants defined by modern thinkers. Evolution of language and aims of substantial practices are showed and new architectural and design styles, like recycling-, pop-, eco-, recreational, motion-, media-design and so on, are marked and characterized. Modern phase of art’s development, that integrates it with other cultural practices, such as science, trade, production, communication, medicine, show-business, tourism, etc., which change its forms and nature (media-art, video-art, transmission-art, technological art (electronic, robot- and genomic-art, internet-art). All these types of architectural, design and artistic activity exist and are fulfilled in kind of intensive fusion, organizing and fundamentally changing human’s habitat.  The variety of design styles are strongly connected today with the commitment to unify form-creating intentions, that had been disconnected during the movement of social progress, which means conformity with modernity’s character and requirements while maintaining ontological basis that gives a human sense of home and self-identity. Designer practices that implement communicative interactive potential in projectivity while keeping spaces alive and human are able to perform this harmony. Hence, exploration of features and vectors of the embodied in real and virtual substance projective activity gives a deeper understanding of the sense of civilizational transformations and their connection with human’s substantive dimensions.
Keywords: culture, cultural practices, prosumption, participation, multimedia and multisensory design, e-culture, hybrid art